Tingkat Kepuasan Siswa Terhadap Permainan Truth or Dare Berbasis Problem Based Learning - Ratnasari, Hesty; Rodliyah, Iesyah (Jurnal Axioma : Jurnal Matematika dan Pembelajaran, 2024)
Learning media that is less interesting can trigger bad responses given by students during learning. One of the interesting learning media for students is through games. This research uses descriptive quantitative methods to describe the level of student satisfaction after participating in learning using problem-based learning-based truth or dare games. The data collection technique in this research is in the form of a questionnaire containing closed statements and includes 3 indicators using a Likert scale. This research was carried out at SMPN 2 Sumobito with research subjects in class VII-C even semester of 2023/2024. The results obtained were that the cognitive indicators produced a percentage value of 79% (very strong), affective 79% (very strong), and conative 81% (very strong). The overall response value percentage is 80% in the very strong category. Keywords: Truth or Dare, Problem-Based Learning (PBL), Level of Satisfaction